1998
DOI: 10.1046/j.1365-2230.1998.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse necrobiosis lipoidica diabeticorum associated with non-insulin dependent diabetes mellitus

Abstract: We report a case of diffuse necrobiosis lipoidica (NL) which first appeared on the legs and scrotum, before gradually spreading across the back and arms; the patient also suffered from diabetes mellitus, and the NL lesion began to disappear as the diabetes mellitus was controlled. The possible contribution of various glycation and glycoxidation products of collagen to the pathogenesis of NL is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
(4 reference statements)
0
16
0
1
Order By: Relevance
“…The legs are most commonly affected. It has been reported that NLD resolves with good control of diabetes [1,2]. Here we report an unusual case in which NLD developed in the periorbital region.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The legs are most commonly affected. It has been reported that NLD resolves with good control of diabetes [1,2]. Here we report an unusual case in which NLD developed in the periorbital region.…”
Section: Introductionmentioning
confidence: 73%
“…The legs are most frequently affected, but NLD can also involve the hands, fingers, and forearms [1,2]. Scalp involvement has been reported in a few cases [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of necrobiosis lipoidica remains unclear. A proposed role for autoimmunity exists based on demonstration of IgM and immune complexes within NL lesions and dermal microvessels (5,7,9). It may be due to diabetic microangiopathy (1, 6, 7) or a hypoxia-induced vasculopathy (5).…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to diabetic microangiopathy (1, 6, 7) or a hypoxia-induced vasculopathy (5). Multiple collagen abnormalities have been noted in NL plaques, including abnormal collagen production (1), the accelerated glycation and oxidation of collagen seen in diabetic skin and subsequent increased collagen cross-linking following oxidation (7). Whether it is a primary collagen disorder, or secondary to diabetic changes, NL may be due to collagen degeneration with secondary inflammation and granulomatous change (5, 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation